اسلامی عدالتی نظام میں القضاء علی الغائب: فقہی و تاریخی مطالعہ: Ex Parte Judgment in the Islamic Judicial System: A Juristic and Historical Study - Dr. Sobia Nosheen (Al-Amīr Research Journal for Islamic Studies, 2025)
“Ex parte decision” (Qaḍāʾ ʿalā al-Ghāʾib) represents one of the most significant and debated concepts in the Islamic judicial system. It refers to a judicial ruling issued in the absence of a party, which may give rise to multiple interpretative viewpoints. Despite its complexities, such decisions serve as a cornerstone for protecting the rights of individuals and ensuring the continuity of judicial processes. This study provides a comprehensive analysis of the development of ex parte judgments, tracing their origins from the Prophetic era and examining their evolution through the Abbasid period and subsequent Islamic legal practice. The article examines juristic similarities and differences, explores remedial mechanisms, and highlights the rights and safeguards afforded to absent parties. In addition, the research incorporates the perspectives of contemporary ʿUlamāʾ, providing a critical evaluation of the practical application of ex parte rulings in the Islamic judicial system, particularly in the context of the Subcontinent and Pakistan. Keywords: Qur’an, Hadith, Qaḍāʾ al-Ghāʾib, Ibn Qudāmah, Wahbah al-Zuḥaylī, Islamic judicial system, Subcontinent, Pakistan.